Prevalence of Periodontitis among the People with Diabetes Mellitus - Pant, Bhawana Neupane; Goit, Rajesh Kumar; Satyal, Biswas; Poudel, Abhishek (Journal of Nepalgunj Medical College, 2021)
Introduction: Diabetes mellitus is a metabolic disorder characterized by a chronic high level of blood sugar with disturbances in carbohydrate, fat, and protein metabolism resulting from defects in insulin secretion, action or both. Periodontitis is a chronic infectious disease which leads to the destruction of the periodontal ligament fibers and alveolar bone until tooth loss. Among the several factors that may manifest periodontitis like aging, genetic factors, poor oral hygiene, obesity and virulence of the attacking micro-organisms, type 2 diabetes mellitus has received the greatest attention.Aims: The aim of the study was to determine the association type 2 diabetes mellitus with periodontal condition among population in mid-western region of Nepal.Methods: We screened 200 subjects of age group from 30 to 50 years and divided into two groups:  Group I – diabetic person and Group II were non diabetic. Oral examination was done to get the Community Periodontal Index of Treatment Need score and correlation between Diabetes mellitus and periodontal disease was determined.Results: Our result showed strong correlation between diabetes mellitus and periodontitis. When the evaluation was done for prevalence of periodontal disease according to diabetes mellitus,  the prevalence of periodontal disease was significantly higher in diabetic person compared to non-diabetic individuals (88% vs 74.4%, P=0.03).  [Odds Ratio = 11.826 and 95% confidence interval: 5.415-21.828].Conclusion: Provided Diabetes mellitus related morbidity and mortality is burgeoning in our society and it is imperative to identify right indicators of periodontal disease for specific population.